Identifikasi dan Konsep Pengembangan Kawasan Ruang Terbuka Hijau (RTH) Kota Padangsidimpuan - Yunita Syafitri Rambe (ARSITEKTURA, 2020)
Urban areas in Indonesia tend to experience a typical problem, namely the high rate of population growth due to urbanization which causes the management of urban space to become increasingly difficult. The high and increasing number of urban population has implications for the high pressure on the use of urban space, so that it is necessary to organize the space in urban areas, especially public and social facilities as well as public open spaces in urban areas. Padangsidimpuan City is one of the cities in North Sumatra Province that has green open spaces but has not received special attention. So it is necessary to do research on identification and development. This is done with the aim of creating a comfortable, productive and sustainable urban space to create a sustainable existence of public open spaces in urban areas. The method used in this research is qualitative and quantitative methods with literature, interview, survey and recording techniques which later the data obtained will be analyzed for the development of green open spaces (RTH). It is hoped that the results of this research will be useful as a basic foundation for interested parties in developing and in further research.